Charakterystyka wad refrakcji u osób badanych przez Terenową Wojskową Komisję Lekarską w Łodzi - Nowak, Michał S.; Goś, Roman; Śmigielski, Janusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To determine the prevalence of refractive errors in population. Material and methods: A retrospective review of medical examinations for entry to the military service from The Area Military Medical Commission in Lodz. Ophthalmic examinations were performed. We used statistic analysis to review the results. Results: Statistic analysis revealed that refractive errors occurred in 21.68% of the population. The most commen refractive error was myopia. Conclusions: 1) The most commen ocular diseases are refractive errors, especially myopia (21.68% in total). 2) Refractive surgery and contact lenses should be allowed as the possible correction of refractive errors for military service.